Cooperative Game Theory of Hierarchies: One Approach to Solving the Low-Risk Puzzle? - Tobias Hiller (Risks)
In this article, we extend the application of cooperative game theory to the so-called low-risk puzzle. Specifically, we apply concepts that consider hierarchies on the assets in the allocation of portfolio risk. These hierarchies have not previously been considered in portfolio risk allocation using cooperative game theory. We demonstrate our idea through a simulation study. Our results show that considering hierarchies can contribute to solving the low-risk puzzle. Our findings may advance further developments in portfolio theory.